Dynamic reliability analysis of a heat-roller based on finite element method. Issue 1 (January 2020) - Wen, Guang; Liu, Pingping; Zuo, Fangjun; Su, Rui; Jia, Meiwei; Li, Gangjun; Kang, Zeyu
Abstract: Taking a heat-roller of a laser printer as the research object, the dynamic characteristics and reliability were analyzed by using the finite element software ANSYS. Through modal analysis, it can be concluded that the first eighth natural frequencies of the heat-roller are 1343, 1365, 3612, 3677, 6885, 7001, 7168, 10634 Hz. The corresponding modal modes are as follows: except that the fifth mode is the torsional mode of the structure, the other modes are the bend mode. Through the harmonic response analysis, it can be concluded that the first mode has the greatest influence on the dynamic characteristics of the structure. The sensitivity analysis results show that the material characteristics and size parameters which have great influence on the dynamic characteristics of the structure are l 2, den, ex, d 1, d 3 and x .